The Impact of the COVID-19 Pandemic on Pediatric Dentistry: Insights from an Italian Cross-Sectional Survey - Giulio Conti; Francesca Amadori; Alessandra Bordanzi; Alessandra Majorana; Elena Bardellini (MDPI AG, 2023)
Background. The COVID-19 pandemic has had a significant impact on pediatric dentistry and also dental education. This study aimed to assess the observed changes in children's oral health by pediatric dentists and also served as an educational tool for dentistry students during the pandemic. Methods. Postgraduate students in pediatric dentistry prepared a survey addressed to Italian pediatric dentists. Over 5476 dentists were invited to participate, and collaboration among the students took place through virtual meetings and electronic platforms. The online questionnaire was composed of 29 questions focusing on the management of pediatric patients during and after the lockdown period. A descriptive statistic was used for data analysis, and chi-square tests were performed (p < 0.05). Results. A total of 1752 pediatric dentists participated in the survey. During the lockdown, 68.3% of dentists exclusively handled dental emergencies. In the subsequent semester, a significant decrease in the number of pediatric treatments was reported. Pediatric dentists also noted a decline in children's oral hygiene practices, a deterioration in dietary habits, and an increase in anxiety during dental procedures. Conclusions. This survey shed light on the diverse effects of the pandemic on children's oral health and also provided valuable educational insights.